2012
DOI: 10.1021/ac202715f
|View full text |Cite
|
Sign up to set email alerts
|

On Chip Droplet Characterization: A Practical, High-Sensitivity Measurement of Droplet Impedance in Digital Microfluidics

Abstract: We demonstrate a new approach to impedance measurement on digital microfluidics chips for the purpose of simple, sensitive, and accurate volume and liquid composition measurement. Adding only a single series resistor to existing AC droplet actuation circuits, the platform is simple to implement and has negligible effect on actuation voltage. To accurately measure the complex voltage across the resistor (and hence current through the device and droplet), the designed system is based on software-implemented lock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 36 publications
0
49
0
Order By: Relevance
“…However, because [ 18 F]fallypride synthesized by EWOD has some of the highest reported specific activity (19 Ci/µmole), fluorine-19 contamination from Teflon® appears not likely to be a major issue [23].…”
Section: Device Description and Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because [ 18 F]fallypride synthesized by EWOD has some of the highest reported specific activity (19 Ci/µmole), fluorine-19 contamination from Teflon® appears not likely to be a major issue [23].…”
Section: Device Description and Fabricationmentioning
confidence: 99%
“…Past reports have demonstrated a range of droplet functions (i.e., generating, moving, splitting, and merging) [17], precise control of droplet volumes [18], on chip liquid composition measurement [19], and suitability for multiple reagent chemical synthesis [20]. Our group has recently reported the use of EWOD for the synthesis of the most commonly used PET radiotracer, [ 18 F]FDG [21].…”
Section: Introductionmentioning
confidence: 99%
“…An in-depth investigation led to the observation that the dependence of SA on reaction parameters was very different for macroscale (100-5000 μL) and microscale (2-8 μL) syntheses. At the macroscale, the SA strongly varied with the reaction volume (amount of reagents) as well as the starting radioactivity (from 10s to 100 s of mCi), whereas the SA was much higher and nearly constant (20)(21)(22)(23) Ci/μmol), under all conditions when performed in microdroplets. These results suggest that in the macroscale synthesis, reagents and solvents are the dominant source of fluorine-19, while in microscale volumes, these sources have been nearly eliminated and the fluorine-19 contribution from the cyclotron dominates [44,45] (Fig.…”
Section: High Specific Activitymentioning
confidence: 99%
“…In preliminary studies, our group observed that microfluidic synthesis on EWOD chips resulted in significantly higher (up to 25-50 times) SA compared to macroscale synthesis, starting with the same amount of radioactivity [23,24]. This suggested the potential for microfluidics to significantly reduce fluorine-19 contamination in the synthesis process.…”
Section: High Specific Activitymentioning
confidence: 99%
“…In order to manipulate droplets in DMF devices, the droplet must be grounded and at least a portion of the contact line of the interface must be above the active electrode (Mugele and Baret 2005;Nelson and Kim 2012;Choi et al 2012). In the most common configuration, each addressable location in the device can be modeled as a resistor and capacitor in parallel (Lederer et al 2012;Sadeghi et al 2012;Schertzer et al 2012;Shih et al 2013). As such, previous investigations have used capacitance (Su et al 2004;Ren et al 2004;Su et al 2005;Gong and Kim 2008;Shih et al 2011;Yafia and Najjaran 2013) and impedance (Lederer et al 2012;Sadeghi et al 2012;Schertzer et al 2012;Shih et al 2013) measurements to provide real-time feedback at every addressable position in the device without requiring optical access, or increasing fabrication complexity.…”
Section: Introductionmentioning
confidence: 99%